MENUMBUHKAN JIWA KEPEMIMPINAN OSIS SMP NEGERI 16 JAKARTA YANG BERTANGGUNG JAWAB DAN VISIONER - Mahendrawan, Ersam; Rahmawati, Sholichatun Aisah; Riyandy, Riyandy; Siregar, Rohani; Tamami, Sofyan; Erwin, Tarub (Yayasan Education and Social Center, 2024)
Community service is a crucial pillar of the Tri Dharma of Higher Education, playing a vital role in community development and education. This program, conducted by graduate students from Pamulang University’s Master of Educational Management, aimed to cultivate leadership qualities among students at SMPN 16 Jakarta through their participation in OSIS. The initiative focused on nurturing leadership that is visionary, responsible, and proactive in facing challenges both in school and in the broader community.Through interactive methods such as lectures, group discussions, and practical simulations, students were encouraged to understand the core values of character-driven leadership. The training emphasized the importance of integrity, effective communication, and problem-solving skills that are both creative and collective. Furthermore, students were taught how to become visionary leaders, capable of foreseeing the future and crafting strategic steps to achieve shared goals. By fostering responsible leadership qualities, students not only learned to manage an organization but also how to become agents of change, positively impacting their surroundings. This program aspires to shape future leaders who are intelligent, visionary, and possess a strong sense of integrity, capable of contributing to sustainable community development.